2020
DOI: 10.1111/apha.13530
|View full text |Cite
|
Sign up to set email alerts
|

Intact vagal gut‐brain signalling prevents hyperphagia and excessive weight gain in response to high‐fat high‐sugar diet

Abstract: Aim The tools that have been used to assess the function of the vagus nerve lack specificity. This could explain discrepancies about the role of vagal gut‐brain signalling in long‐term control of energy balance. Here we use a validated approach to selectively ablate sensory vagal neurones that innervate the gut to determine the role of vagal gut‐brain signalling in the control of food intake, energy expenditure and glucose homoeostasis in response to different diets. Methods Rat nodose ganglia were injected bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 108 publications
4
33
0
Order By: Relevance
“…We also observed that tVNS did not change liking or wanting for stimuli varying in sugar content. This is in line with the observation that vagal deafferentation of the gut results in increased food intake after a fat but not sugar preload (McDougle et al, 2020), and may suggest a more prominent role for the vagus nerve in signaling fat content to the brain. However, it is also possible that the fixed order of non-fatty sweet Jell-O samples presentation after fatty puddings samples may have worked against observing effects on sweetness perception, as a reduction in fat levels may result in a reduction of perceived sweetness (Wiet et al, 1993;Biguzzi et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that tVNS did not change liking or wanting for stimuli varying in sugar content. This is in line with the observation that vagal deafferentation of the gut results in increased food intake after a fat but not sugar preload (McDougle et al, 2020), and may suggest a more prominent role for the vagus nerve in signaling fat content to the brain. However, it is also possible that the fixed order of non-fatty sweet Jell-O samples presentation after fatty puddings samples may have worked against observing effects on sweetness perception, as a reduction in fat levels may result in a reduction of perceived sweetness (Wiet et al, 1993;Biguzzi et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…At the same time, vagotomy-induced overeating is often transient, presumably due to compensatory changes at the central level ( Walls et al, 1995 ; Chavez et al, 1997 ; Phillips and Powley, 1998 ; Zafra et al, 2003 ; Reidelberger et al, 2014 ). Instead, in normal-weight animals, long-term vagotomy and deafferentation have been reported to result in animals eating smaller meals, with some degree of anorexia and weight loss ( Mordes et al, 1979 ; Sclafani and Kramer, 1985 ; Kraly et al, 1986 ; Erecius et al, 1996 ; Leonhardt et al, 2004 ; Powley et al, 2005a ; McDougle et al, 2020 ). Interestingly, eating smaller meals post-vagotomy is often compensated by more frequent meals, further suggesting significant brain adaptations ( Powley et al, 2005a ).…”
Section: Satiation Without a Vagus Nervementioning
confidence: 99%
“…It has often been argued, with good reasons, that vagotomies, especially when vagal (motor) efferents are involved, are difficult to interpret because of secondary dysmotility, malaise, and dyspepsia ( Sclafani et al, 1981 ; McDougle et al, 2020 ). At the same time, the latter factors could not entirely account for reduced food intake and weight loss ( Mordes et al, 1979 ; Sclafani and Kramer, 1985 ).…”
Section: Satiation Without a Vagus Nervementioning
confidence: 99%
“…However, we did not find changes in Mch1r nor Cb1r gene expression in VAN GHSR KD rats compared with controls, suggesting that dysregulation of these receptors is not contributing to the meal pattern changes observed. Notably, ablation of cholecystokinin (CCK) receptorexpressing VAN, which overlap substantially with GHSR-positive VAN [9], produces similar increases in meal frequency without affecting meal size [41]. While CCKR expression was not measured in the present study, the possibility that GHSR and CCKR interact in VAN to influence meal frequency is unlikely given that VAN GHSR KD did not affect VAN neural responses to gut-restricted CCK.…”
Section: Previous Work Shows That Ghrelin Blocks the Downregulation Omentioning
confidence: 67%